“É o Nosso Pedaço da África, Uai”. A Bahia no Imaginário Candomblecista de Uberaba (MG) - Dias, João Ferreira (Trabalhos de Antropologia e Etnologia, 2020)
It is well-known that Africa invokes a series of mental-emotional and political dispositions among candomblé practitioners. It configures, indeed, a truly lieu de mémoire, related to the slave trade, but also an ideological resource for narratives on authenticity. In that sense, it is clear that Africa remains the ultimate source of power for those practitioners. However, despite the validity of that statement, it is my intention to present here the ways in which Uberaba’s candomblé community invokes Bahia as ideological and normative reference.